Analysis of food supplements and sports foods consumption patterns among a sample of gym-goers in Portugal - Sofia Lopes; Madalena Cunha; João Guilherme Costa; Cíntia Ferreira-Pêgo (Taylor & Francis Group, 2024)
Background Gym-goers usually seek methods to improve performance, muscle gain, and overall health. One of the main strategies is including food supplements (FS) into their routine as aids to enhance their athletic capabilities and satisfy their nutritional needs. Thus, this study aimed to investigate and characterize the main FS and Sports Foods (SF) currently consumed, as well as the main reasons for their use and the source of advice in a group of gym-goers in the Lisbon Metropolitan Area (Portugal).Methods A cross-sectional study was conducted, including 303 gym-goers from Lisbon, Portugal, who were 133 women and 170 males (30.8 ± 12.9 years old). Face-to-face interviews were used by qualified researchers to gather data.Results Most of the interviewed athletes (71.95 %) took FS/SF, being men the main consumers. On average, 1.59 supplements were consumed per athlete. Logistic regression models indicated significant associations between age, gender, and motivations for gym attendance. While men and younger groups attended mainly for hypertrophy, women and older groups were focused on well-being. Protein (59.17 %) was the most used FS/SF, followed by creatine (41.28 %) and multivitamins (27.06 %). Men and younger individuals preferred protein and creatine, while older individuals focused more on specific vitamins and minerals. Women seemed to prefer L-carnitine and protein yogurts. Main sources of information included the internet, friends, and dietitians with notable gender and age-based preferences. Online stores were the main place of purchase. Monthly expenditures on FS/SF were not significantly affected by age or gender, but motivations for use had an influence.Conclusion Most of the athletes interviewed took FS/SF, being men the major consumers. Protein was the principal FS/SF used, with online stores being the main place of purchase and the internet the primary source of information. Age and gender were key factors in adopted training, in the FS/SF chosen, and in the source of information selected. It is crucial that health professionals take primary responsibility for providing this guidance.